Role of IRF4 in the Protection of Metformin-Mediated Sepsis Myocarditis - Minghua Li; Hongmei Yu; Yonglin Wang; Ling Qin; Wei Sun (SAGE Publishing, 2019)
Aims: Metformin has been shown to play a protective role in diabetes. However, we found that metformin could mediate myocardial protection. Given that protein kinase C eplison (PKCε) and interferon regulatory factor 4 (IRF4) are critical for cardioprotection signaling. And measurement of fluorescence resonance energy transfer (FRET) efficiency can be used to determine whether 2 fluorophores are within a certain distance of each other. So we sought to determine whether metformin promotes PKCε/IRF4 activation by FRET. Methods and Results: The study built a mouse septic myocarditis model by intraperitoneal injection of Escherichia coli ; thus, it provides valuable experimental data for the diagnosis and treatment of septic myocarditis. And cellular model of cardiomyocyte damage from adult rat cardiacmyocytes or H9c2 cells was induced by lipopolysaccharide employed to examine PKCε by molecular, biochemical, and cellular imaging analysis. Life span of septic myocarditis mouse was significantly prolonged by metformin. Metformin also decreased transforming growth factor β level and increased interleukin-10 productions. The FRET analysis in H9c2 cells suggested that there is prominent FRET signal for PKCε along in mitochondrial by metformin. Conclusion: We demonstrate that metformin promotes rapid association of PKCε with IRF4 at mitochondrial microdomain of cardiac myocytes and PKCε via direct molecular interaction with IRF4. This regulatory mechanism may play an important role in cardioprotection.